Linking rumination and proactive control in reducing implicit racial bias - Ferreira, Maria Inês Lopes (2023)
Implicit racial bias continues to be a central research topic in psychology given its individual and social impact. Interventions designed to reduce bias, namely, the implementation of counter stereotypical intentions (cued proactive control), have shown to be effective. Rumination has been documented as a negative output arising from one’s awareness of the discrepancy between explicit and implicit attitudes. However, the literature is inconsistent regarding the social cognitive theories of rumination. One of the main goals of this study was to deepen our knowledge about the role of rumination on cognitive performance, particularly on an implicit racial paradigm. A common successful procedure in reducing implicit bias – intention manipulation - was replicated, and the Brief Implicit Association Test (BIAT) was used as a pre- and post-manipulation measure of implicit bias. A sample of 104 participants were randomly distributed to two groups in a Weapon Identification Task (WIT) performance: experimental group (intention manipulation - think “safe” when seeing a Black face) and control group (think “quick” when seeing a Black face). Mood and state rumination were assessed at the end of the experiment. The BIAT data evidenced a significantly greater decrease in response time (RT) in the control group, than in the experimental group, from pre- to post-manipulation. The WIT performance data revealed that the participants in the experimental group (intention manipulation) made fewer stereotypical errors and more counter stereotypical errors than the control group. Furthermore, participants with higher brooding presented a significantly higher proportion of counter stereotypical errors and a lower proportion of stereotypical ones. This study seems to reinforce previous findings on the effectiveness of reducing implicit racial bias through proactive control activation, as well as provides initial evidence for the interaction between proactive control and brooding rumination. Given the exploratory nature of this study, further research must be carried out.